O teletrabalho docente na cultura digital e o direito à desconexão - Oliveira, Ricardo Nascimento de (Universidade Federal de São Carlos, 2022)
This research aims to investigate the consequences of teaching telework in the context of digital culture in the light of changes in the Brazilian labor legislation. The intensive use of digital technologies and mobile telecommunication devices has changed life in society, with repercussions on work. This transformation particularly affected the working hours, form and place of work of professors who carry out non-face-to-face activities. Based on a bibliographical survey, on Brazilian legislation, on the Labor Code of Portugal, on Comparative Law and International Human Rights Law standards, the general objective is to analyze, in the context of teaching telework made possible by digital technologies, how are the boundaries between the teacher's professional and personal life. In pursuit of this general objective, five specific objectives were considered: to draw an overview of the transformations in the working hours of teaching teleworkers in the graphocentric digital society of the 21st century; to analyze the factual and legal contours of the phenomenon of invasion of the privacy of teaching teleworkers through work, through TDIC, as well as to observe how their periods of non-work are going (especially in the midst of the Covid-19 pandemic); to analyze the repercussions of the teaching telework situation regarding the load of professional activities and the right to disconnect; to map the rights and duties of teachers, in a situation of telework, within the graphocentric digital society, with regard to the folding of time and space (ubiquity) and the working day (flexibilization, precariousness); draw a comparative profile of the regulation of teaching telework in Brazilian legislation, post-labor reform (Law 13,467, of July 13, 2017), with the Portuguese one (Labor Code), making incursions in Comparative Law and International Human Rights Law, aiming to investigate the improvements that can be made in the national legislation. With regard to methodology, a general literature review was carried out, field research was carried out, using a questionnaire (with objective and open questions) and semi-structured interviews with the participating professors, analyzing the data qualitatively and quantitatively. Documentary analysis of normative texts of International Human Rights Law was also produced, as well as comparative law, covering Brazilian, Portuguese, French, Argentinean, Chilean law. Due to telework and ubiquity, precarious rights are observed, as opposed to promises and real benefits. As a result of the work, it is recommended the inclusion of the right to disconnection in the country's legislation, the implementation of public policies to raise class awareness in favor of better working conditions for teachers, as well as the establishment of equal rights, especially in regarding the workday, between face-to-face workers and teaching teleworkers.
Teacher teleworking in digital culture anda the right to disconnection
Keywords: Teletrabalho docente; Cultura digital; Direito à desconexão; Teaching telework; Digital culture; Right to disconnect; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS SOCIAIS APLICADAS::DIREITO